Pengaruh Profitabilitas, Likuiditas, Struktur Modal, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Lyon Marvin Sonjaya, Sri Dayanti, Elsa Imelda (Jurnal Ekonomi, 2021)
The main purpose of this research is to analyze the effect of profitability, liquidity, capital structure, and firm size towards firm value on listed manufacturing companies in Indonesia Stock Exchange (IDX). The population of this study is from the year of 2018–2020 using 228 data consisting of 76 manufacturing companies. Eviews 12 was used to process data from this research. The result shown in this research indicates that profitability and capital structure have positive significant effects on firm value, and firm size has negative significant effect on firm value. However, liquidity has no negative significant effect on firm value.